Analisis Kesiapan Blended Learning Di Lingkungan Program Studi Teknik Informatika Universitas PGRI Madiun - Riyanto, Slamet; Mumtahana, Hani Atun (STIKOM Tunas Bangsa Pematangsiantar, 2018)
The purpose of this study was to determine the level of preparedness of blended learning in the Informatics Engineering Study Program Environment at the PGRI Madiun University. This study uses a survey research approach with a total sample of 195 people. The research instrument used questionnaires with Likert scale. Data analysis in this study uses descriptive analysis with learning readiness approach adopted from Aydin and Tasci. The result of the research shows that the readiness of blended learning in informatics engineering study program of PGRI Madiun University, for personal factor or dimension is assessed Not ready needs some works. Self-development factors or dimensions are assessed Not ready needs some works. Factors or dimensions of technology are assessed Ready but needs a few improvement. Factors or dimensions of innovation are rated Not ready needs some works.